The Nexus Between Fatigue Indices and Coping Strategies in Sports Among Oyo State Special Athletes - Komolafe, Adebayo Francis (European Scientific Journal, ESJ, 2018)
Disability sports have acquired an indispensable status in the life of many nations and the special athlete as a whole. Special athletes are exposed to a number of intense physical and psychosocial activities and they needed to make use of a set of cognitive and behavioural strategies in order to cope with these challenges and related fatigue. Hitherto, previous studies had focused largely on adaptive sports and effects of sporting activities on persons with disability without establishing a link between disabled athlete’s use of coping strategies and their achievement motivation. Therefore, it is on this premise that this study harps on the relationship between fatigue indices and coping strategies among Oyo State special athletes. Descriptive survey design using purposive sampling technique was employed. Participants of the study include all the registered special athletes in Oyo State comprising of one hundred and twenty three (123) athletes. Two standardized instruments, thus, Modified fatigue impact scale (r=0.384) and Athletic coping skills inventory (r=0.514) were both employed. Altogether, five hypotheses were tested at 0.05 significant level, and parametric statistics, Pearsons Product moment correlation, and multiple regression analysis were used to analyse the data. Findings revealed significant effect of two independent variables on the dependent variable: cognitive style (β=0.294, r=0.514, P<0.05) and psychosocial factors (β=0.236, r=0.499, P<0.05), while modified fatigue impact has no significant relative effect on coping strategies. The composite effect of independent variables (Modified Fatigue Impact, Cognitive style and Psychosocial Factor) on Athletic coping skills was significant ((F(3,119)=166.777) and about 30% of the variation was accounted for by the independent variables as explained by the adjusted R square. It is therefore recommended that the relationship between fatigue indices and coping strategies is high and the higher the individuals rated their coping with fatigue caused by their disabilities, the lower they scored on fatigue experiences. The more they used coping strategies, the more efficient they coped with fatigue.